Energy-saving medium-temperature high-whiteness ceramic clay and preparation process thereof

By accurately controlling the raw material ratio and preparation process of ceramic mud, and using high-temperature calcination and ball milling treatment methods, the problems of high energy consumption, low raw material utilization rate and unstable product performance in ceramic mud production are solved, and the production of high-performance ceramic products is achieved, reducing energy consumption and production costs.

CN119638367APending Publication Date: 2025-03-18CHAOZHOU HONGXING CERAMICS MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411772816.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing ceramic mud production technology has problems such as high energy consumption, low raw material utilization rate, and unstable product performance. In particular, the raw material particle size is uneven, the mixing uniformity, high process energy consumption and complex operation, making it difficult to meet the needs of high-performance ceramic products.

Method used

By accurately controlling the weight of the raw material and the various steps of the preparation process, high-temperature calcination and ball milling treatment are used to ensure uniform particle size of the raw material and improve plasticity and uniformity. The specific steps include calcining the raw material, crushing it into powder, mixing and stirring, slow mixing and stirring of the aqueous phase and the mud phase, and finally cooling to room temperature.

Benefits of technology

It improves the performance and production efficiency of ceramic products, ensures the physical performance and quality stability of the product, while reducing energy consumption and production costs, and reducing the impact on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638367A_ABST
    Figure CN119638367A_ABST
Patent Text Reader

Abstract

The invention provides energy-saving medium-temperature high-white ceramic mud and a preparation process thereof. The energy-saving medium-temperature high-white ceramic mud is prepared from the following raw materials in parts by weight: 42.2 to 43.0 parts of kaolin, 2.0 to 3.0 parts of quartz sand, 4.0 to 6.0 parts of feldspar, 6.4 to 7.0 parts of calcium carbonate, 4.0 to 6.0 parts of clay, 4.8 to 5.2 parts of talcum powder, 4.0 to 5.0 parts of wollastonite, 4.0 to 5.0 parts of magnesium carbonate, 4.0 to 6.0 parts of aluminum oxide and 12.3 to 13.0 parts of water. The plasticity and the uniformity of the ceramic mud can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials and ceramic products, and more specifically to energy-saving medium-temperature high-white ceramic mud and a preparation process thereof. Background Art

[0002] Existing ceramic mud production technologies usually face problems such as high energy consumption, low raw material utilization, and unstable product performance. Traditional ceramic mud preparation methods often rely on a large amount of energy consumption, such as long-term high-temperature calcination and mixing, which not only increases production costs but also places a burden on the environment. At the same time, due to the inaccurate raw material ratio and the inadequate preparation process, the quality and performance of ceramic mud vary greatly, making it difficult to meet the market demand for high-performance ceramic products.

[0003] In the process of implementing the embodiments of the present invention, the inventors found that there are at least the following problems or defects in the prior art: the particle size of the raw materials is uneven, resulting in poor plasticity and uniformity of the mixed ceramic mud; the high-temperature calcination and mixing and stirring processes have high energy consumption and complex operations, which are not conducive to large-scale production; the lack of fine control over the raw material particle size and mixing uniformity during the preparation of ceramic mud affects the quality and performance of the final product. Summary of the invention

[0004] The invention provides an energy-saving medium-temperature high-white ceramic mud and a preparation process thereof.

[0005] In the first aspect of the present invention, there is provided an energy-saving medium-temperature high-white ceramic mud, which is made of the following raw materials in parts by weight: 42.2 to 43.0 parts of kaolin, 2.0 to 3.0 parts of quartz sand, 4.0 to 6.0 parts of feldspar, 6.4 to 7.0 parts of calcium carbonate, 4.0 to 6.0 parts of clay, 4.8 to 5.2 parts of talc, 4.0 to 5.0 parts of wollastonite, 4.0 to 5.0 parts of magnesium carbonate, 4.0 to 6.0 parts of aluminum oxide and 12.3 to 13.0 parts of water.

[0006] Furthermore, the energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 42.2 parts of kaolin, 2.0 parts of quartz sand, 4.0 parts of feldspar, 6.4 parts of calcium carbonate, 4.0 parts of clay, 4.8 parts of talc, 4.0 parts of wollastonite, 4.0 parts of magnesium carbonate, 4.0 parts of aluminum oxide and 12.3 parts of water.

[0007] Furthermore, the energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 43.0 parts of kaolin, 3.0 parts of quartz sand, 5.0 parts of feldspar, 7.0 parts of calcium carbonate, 6.0 parts of clay, 5.2 parts of talc, 5.0 parts of wollastonite, 5.0 parts of magnesium carbonate, 6.0 parts of aluminum oxide and 13.0 parts of water.

[0008] Furthermore, the energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 42.8 parts of kaolin, 2.6 parts of quartz sand, 5.2 parts of feldspar, 6.8 parts of calcium carbonate, 5.1 parts of clay, 5.0 parts of talc, 4.5 parts of wollastonite, 4.5 parts of magnesium carbonate, 4.5 parts of aluminum oxide and 13.0 parts of water.

[0009] Furthermore, the alumina is a combination of one or more of α-alumina, β-alumina, and γ-alumina.

[0010] Furthermore, the alumina is a mixture of α-alumina and β-alumina, and the weights of the α-alumina and the β-alumina are equal.

[0011] Furthermore, the alumina is γ-alumina, and in parts by weight, the feldspar comprises 4.0 parts and the alumina comprises 6.0 parts.

[0012] Furthermore, the alumina is α-alumina, and the purity of the α-alumina is greater than 99.5%.

[0013] In a second aspect of the present invention, a method for preparing energy-saving medium-temperature high-white ceramic mud is provided, comprising the following steps: S1. The quartz sand and feldspar are calcined at high temperature for 30 to 60 minutes and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 1.5 to 2 hours, then simmered for 3 to 6 hours as the aqueous phase; S4. The clay and alumina were mixed and stirred for 10-20 minutes and kept warm at 70°C to 80°C in a water bath as a mud phase; S5. Slowly pour the aqueous phase into the mud phase, add calcium carbonate and mix, stirring at 150 ℃ ~ 200 ℃ for 20 to 30 minutes; S6. Finally cool to room temperature.

[0014] Furthermore, in step S2, the particle size of the powder is less than 400 mesh, and the powder is ball-milled in a ball mill for 2 to 4 hours to improve the uniformity and plasticity of the raw material; the ball-milled powder is sieved through a 0.5 to 1.0 mm sieve to ensure the consistency of the powder fineness.

[0015] According to the above embodiments of the present invention, at least the following beneficial effects are achieved: by precisely controlling the weight of the raw materials and the various steps of the preparation process, the energy-saving medium-temperature high-white ceramic mud of the present invention can improve the performance and production efficiency of ceramic products. The process of high-temperature calcination and ball milling can ensure that the particle size of the raw materials is uniform, improve their plasticity and uniformity, so that the final product has better physical properties and more stable quality. In addition, by optimizing the raw material ratio, the dependence on energy can be reduced, the production cost can be reduced, and the impact on the environment can be reduced.

[0016] The energy-saving medium-temperature high-white ceramic mud preparation method of the present invention can improve the uniformity of raw materials and the molding quality of products by refining raw material processing and accurately controlling the temperature and time of mixing and stirring. The mixing and stirring of the water phase and the mud phase are carried out at a specific temperature, which helps to form a more uniform and stable ceramic mud, thereby improving the strength and durability of ceramic products. This method can not only improve production efficiency, but also help reduce energy consumption in the production process, achieving the goals of energy saving and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which: Figure 1 A schematic flow chart of a method for preparing energy-saving medium-temperature high-white ceramic mud provided in one embodiment of the present invention. DETAILED DESCRIPTION

[0018] The principles and spirit of the present invention will be described below with reference to several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive characteristics and / or steps, can be combined in any way, unless otherwise described, and can be replaced by other equivalent or alternative features with similar purposes, that is, unless otherwise described, each feature is only one embodiment in a series of equivalent or similar features.

[0020] Example 1: An energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 42.5 parts of kaolin, 2.5 parts of quartz sand, 5.0 parts of feldspar, 6.7 parts of calcium carbonate, 5.0 parts of clay, 5.0 parts of talc, 4.5 parts of wollastonite, 4.5 parts of magnesium carbonate, 3.0 parts each of α-alumina and β-alumina, and 12.5 parts of water.

[0021] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1000 ° C for 45 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 3 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.75 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powders, water, mixed, stirred, heated, boiled over high heat for 1.75 hours, then simmered for 4.5 hours as the aqueous phase; S4. The clay, α-alumina and β-alumina were mixed and stirred for 15 minutes and kept at 75°C in a water bath as a mud phase; S5. Slowly pour the water phase into the mud phase, add calcium carbonate and mix, and stir at 175 ° C for 25 minutes; S6. Finally cool to room temperature.

[0022] In this embodiment, the purity of α-alumina and β-alumina is greater than 99.5%, ensuring the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0023] Reaction conditions: high temperature calcination for 45 minutes, high heat boiling for 1.75 hours, low heat simmering for 4.5 hours, mud phase insulation at 75°C, final mixing and stirring temperature of 175°C.

[0024] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0025] Purity: X-ray diffraction (XRD) analysis shows that the purity of both α-alumina and β-alumina is 99.5%.

[0026] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0027] Example 2: An energy-saving medium-temperature high-white ceramic mud is made from the following raw materials in parts by weight: 42.2 parts of kaolin, 2.0 parts of quartz sand, 4.0 parts of feldspar, 6.4 parts of calcium carbonate, 4.0 parts of clay, 4.8 parts of talc, 4.0 parts of wollastonite, 4.0 parts of magnesium carbonate, 4.0 parts of aluminum oxide and 12.3 parts of water.

[0028] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1100 ° C for 30 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 2 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.5 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 1.5 hours, then simmered for 3 hours as the aqueous phase; S4. The clay and alumina were mixed and stirred for 10 minutes and kept warm at 70°C in a water bath as the mud phase; S5. Slowly pour the water phase into the mud phase, add calcium carbonate and mix, stir at 150 ° C for 20 minutes; S6. Finally cool to room temperature.

[0029] In this embodiment, the alumina is α-alumina, and its purity is greater than 99.5%, which ensures the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0030] Reaction conditions: high temperature calcination for 30 minutes, high heat boiling for 1.5 hours, low heat simmering for 3 hours, mud phase insulation at 70°C, final mixing and stirring temperature of 150°C.

[0031] Yield: The theoretical yield is 100%, and the actual yield is 96%.

[0032] Purity: The purity of α-alumina is 99.8% as determined by X-ray diffraction (XRD) analysis.

[0033] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0034] Example 3: An energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 43.0 parts of kaolin, 3.0 parts of quartz sand, 5.0 parts of feldspar, 7.0 parts of calcium carbonate, 6.0 parts of clay, 5.2 parts of talc, 5.0 parts of wollastonite, 5.0 parts of magnesium carbonate, 6.0 parts of aluminum oxide and 13.0 parts of water.

[0035] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1200 ° C for 60 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 4 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 1.0 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 2 hours, then simmered for 6 hours as the aqueous phase; S4. The clay and alumina were mixed and stirred for 20 minutes and kept warm at 80°C in a water bath as the mud phase; S5. Slowly pour the aqueous phase into the mud phase, add calcium carbonate and mix, stirring at 200 ° C for 30 minutes; S6. Finally cool to room temperature.

[0036] In this embodiment, the alumina is γ-alumina, and its purity is greater than 99.5%, which ensures the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0037] Reaction conditions: high temperature calcination for 60 minutes, high heat boiling for 2 hours, low heat simmering for 6 hours, mud phase insulation at 80°C, and final mixing and stirring temperature at 200°C.

[0038] Yield: The theoretical yield is 100%, and the actual yield is 95%.

[0039] Purity: The purity of γ-alumina is 99.8% as determined by X-ray diffraction (XRD) analysis.

[0040] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0041] Example 4: An energy-saving medium-temperature high-white ceramic mud is made from the following raw materials in parts by weight: 42.8 parts of kaolin, 2.6 parts of quartz sand, 5.2 parts of feldspar, 6.8 parts of calcium carbonate, 5.1 parts of clay, 5.0 parts of talc, 4.5 parts of wollastonite, 4.5 parts of magnesium carbonate, 4.5 parts of aluminum oxide and 13.0 parts of water.

[0042] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1150 ° C for 45 minutes and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 3.5 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.75 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powders, water, mixed, stirred, heated, boiled over high heat for 1.75 hours, then simmered for 4.5 hours as the aqueous phase; S4. The clay and alumina were mixed and stirred for 15 minutes and kept warm at 75°C in a water bath as the mud phase; S5. Slowly pour the water phase into the mud phase, add calcium carbonate and mix, and stir at 175 ° C for 25 minutes; S6. Finally cool to room temperature.

[0043] In this embodiment, the alumina is a mixture of α-alumina and β-alumina, and the weight of the two is equal, which ensures the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0044] Reaction conditions: high temperature calcination for 45 minutes, high heat boiling for 1.75 hours, low heat simmering for 4.5 hours, mud phase insulation at 75°C, final mixing and stirring temperature of 175°C.

[0045] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0046] Purity: X-ray diffraction (XRD) analysis shows that the purity of both α-alumina and β-alumina is 99.5%.

[0047] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0048] Example 5: An energy-saving medium-temperature high-white ceramic mud is made from the following raw materials in parts by weight: 42.2 parts of kaolin, 2.0 parts of quartz sand, 4.0 parts of feldspar, 6.4 parts of calcium carbonate, 4.0 parts of clay, 4.8 parts of talc, 4.0 parts of wollastonite, 4.0 parts of magnesium carbonate, 3.0 parts each of α-alumina and β-alumina, and 12.3 parts of water.

[0049] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1100 ° C for 50 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 3 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.5 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 1.5 hours, then simmered for 4 hours as the aqueous phase; S4. The clay, α-alumina and β-alumina were mixed and stirred for 15 minutes and kept at 75°C in a water bath as a mud phase; S5. Slowly pour the aqueous phase into the mud phase, add calcium carbonate and mix, stirring at 180 ° C for 25 minutes; S6. Finally cool to room temperature.

[0050] In this embodiment, the mixture of α-alumina and β-alumina ensures the high performance and stability of the ceramic mud, and the weight of α-alumina and β-alumina is equal. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0051] Reaction conditions: high temperature calcination for 50 minutes, high heat boiling for 1.5 hours, low heat simmering for 4 hours, mud phase insulation at 75°C, final mixing and stirring temperature at 180°C.

[0052] Yield: The theoretical yield is 100%, and the actual yield is 96%.

[0053] Purity: X-ray diffraction (XRD) analysis shows that the purity of both α-alumina and β-alumina is 99.5%.

[0054] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0055] Example 6: An energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 42.2 parts of kaolin, 2.0 parts of quartz sand, 4.0 parts of feldspar, 6.4 parts of calcium carbonate, 4.0 parts of clay, 4.8 parts of talc, 4.0 parts of wollastonite, 4.0 parts of magnesium carbonate, 6.0 parts of γ-alumina and 12.3 parts of water.

[0056] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1100 ° C for 40 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 3 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.5 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 1.5 hours, then simmered for 3 hours as the aqueous phase; S4. The clay and γ-alumina were mixed and stirred for 15 minutes and kept warm at 75°C in a water bath as a mud phase; S5. Slowly pour the aqueous phase into the mud phase, add calcium carbonate and mix, and stir at 190 ° C for 25 minutes; S6. Finally cool to room temperature.

[0057] In this embodiment, the purity of γ-alumina is greater than 99.5%, ensuring the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0058] Reaction conditions: high temperature calcination for 40 minutes, high heat boiling for 1.5 hours, low heat simmering for 3 hours, mud phase insulation at 75°C, final mixing and stirring temperature at 190°C.

[0059] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0060] Purity: The purity of γ-alumina is 99.8% as determined by X-ray diffraction (XRD) analysis.

[0061] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0062] Example 7: An energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 43.0 parts of kaolin, 3.0 parts of quartz sand, 4.0 parts of feldspar, 7.0 parts of calcium carbonate, 6.0 parts of clay, 5.2 parts of talc, 5.0 parts of wollastonite, 5.0 parts of magnesium carbonate, 6.0 parts of α-alumina and 13.0 parts of water.

[0063] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1150 ° C for 55 minutes and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 3.5 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.8 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 2 hours, then simmered for 5 hours as the aqueous phase; S4. The clay and α-alumina were mixed and stirred for 20 minutes and kept warm at 80°C in a water bath as a mud phase; S5. Slowly pour the water phase into the mud phase, add calcium carbonate and mix, and stir at 195°C for 30 minutes; S6. Finally cool to room temperature.

[0064] In this embodiment, the purity of α-alumina is greater than 99.5%, ensuring the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0065] Reaction conditions: high temperature calcination for 55 minutes, high heat boiling for 2 hours, low heat simmering for 5 hours, mud phase insulation at 80°C, and final mixing and stirring temperature of 195°C.

[0066] Yield: The theoretical yield is 100%, and the actual yield is 96%.

[0067] Purity: The purity of α-alumina is 99.8% as determined by X-ray diffraction (XRD) analysis.

[0068] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0069] Example 8: An energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 42.8 parts of kaolin, 2.6 parts of quartz sand, 5.2 parts of feldspar, 6.8 parts of calcium carbonate, 5.1 parts of clay, 5.0 parts of talc, 4.5 parts of wollastonite, 4.5 parts of magnesium carbonate, 4.5 parts of α-alumina and 13.0 parts of water.

[0070] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1100 ° C for 50 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 3 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.6 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powders, water, mixed, stirred, heated, boiled over high heat for 1.75 hours, then simmered for 4 hours as the aqueous phase; S4. The clay and α-alumina were mixed and stirred for 18 minutes and kept warm at 77°C in a water bath as a mud phase; S5. The aqueous phase is slowly poured into the mud phase, and calcium carbonate is added and mixed and stirred at 185°C for 28 minutes; S6. Finally cool to room temperature.

[0071] In this embodiment, the purity of α-alumina is greater than 99.5%, ensuring the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0072] Reaction conditions: high temperature calcination for 50 minutes, high heat boiling for 1.75 hours, low heat simmering for 4 hours, mud phase insulation at 77°C, final mixing and stirring temperature of 185°C.

[0073] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0074] Purity: X-ray diffraction (XRD) analysis shows that the purity of α-alumina is 99.9%.

[0075] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0076] like Figure 1Example 9: A method for preparing energy-saving medium-temperature high-white ceramic mud, wherein the energy-saving medium-temperature high-white ceramic mud is made of the following raw materials in parts by weight: 42.0 parts of kaolin, 2.5 parts of quartz sand, 4.5 parts of feldspar, 6.5 parts of calcium carbonate, 4.5 parts of clay, 4.9 parts of talc, 4.6 parts of wollastonite, 4.7 parts of magnesium carbonate, 5.0 parts of aluminum oxide and 12.5 parts of water.

[0077] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1100 ° C for 40 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 2.5 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.6 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 1.5 hours, then simmered for 3.5 hours as the aqueous phase; S4. The clay and alumina were mixed and stirred for 15 minutes and kept warm at 75°C in a water bath as the mud phase; S5. Slowly pour the water phase into the mud phase, add calcium carbonate and mix, and stir at 175 ° C for 25 minutes; S6. Finally cool to room temperature.

[0078] In this embodiment, the alumina is α-alumina, and its purity is greater than 99.5%, which ensures the high performance and stability of the ceramic mud. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0079] Reaction conditions: high temperature calcination for 40 minutes, high heat boiling for 1.5 hours, low heat simmering for 3.5 hours, mud phase insulation at 75°C, final mixing and stirring temperature of 175°C.

[0080] Yield: The theoretical yield is 100%, and the actual yield is 96%.

[0081] Purity: The purity of α-alumina is 99.8% as determined by X-ray diffraction (XRD) analysis.

[0082] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0083] Example 10: A method for preparing energy-saving medium-temperature high-white ceramic mud, which is made of the following raw materials in parts by weight: 42.0 parts of kaolin, 2.5 parts of quartz sand, 4.5 parts of feldspar, 6.5 parts of calcium carbonate, 4.5 parts of clay, 4.9 parts of talc, 4.6 parts of wollastonite, 4.7 parts of magnesium carbonate, 4.8 parts of α-alumina and 12.5 parts of water.

[0084] The preparation method of this embodiment comprises the following steps: S1. The quartz sand and feldspar are calcined at a high temperature of 1100 ° C for 45 minutes, and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder, the particle size of the powder is less than 400 mesh, and the powder is ball milled in a ball mill for 3 hours to improve the uniformity and plasticity of the raw materials; the ball milled powder is sieved through a 0.5 mm sieve to ensure the consistency of the powder fineness; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 1.5 hours, then simmered for 3 hours as the aqueous phase; S4. The clay and α-alumina were mixed and stirred for 15 minutes and kept warm at 75°C in a water bath as a mud phase; S5. Slowly pour the aqueous phase into the mud phase, add calcium carbonate and mix, stirring at 180 ° C for 25 minutes; S6. Finally cool to room temperature.

[0085] In this embodiment, the particle size of the powder is less than 400 mesh, and the powder is ball-milled in a ball mill for 2 to 4 hours to improve the uniformity and plasticity of the raw material; the powder after ball milling is sieved through a 0.5 to 1.0 mm sieve to ensure the consistency of the powder fineness. Experimental data: Synthesis method: Follow the above steps S1 to S6.

[0086] Reaction conditions: high temperature calcination for 45 minutes, high heat boiling for 1.5 hours, low heat simmering for 3 hours, mud phase insulation at 75°C, final mixing and stirring temperature at 180°C.

[0087] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0088] Purity: The purity of α-alumina is 99.8% as determined by X-ray diffraction (XRD) analysis.

[0089] Uses and effects: This energy-saving medium-temperature high-white ceramic mud is suitable for the fields of construction and ceramic products. Experiments show that products made from this ceramic mud have lower thermal conductivity and higher mechanical strength, can effectively save energy consumption and improve production efficiency.

[0090] Comparative Example 1 This comparative example is a traditional ceramic mud, which is prepared from the following raw materials in parts by weight: 40 parts of kaolin, 5 parts of quartz sand, 6 parts of feldspar, 8 parts of calcium carbonate, 5 parts of clay, 5 parts of talc, 5 parts of wollastonite, 5 parts of magnesium carbonate, 5 parts of aluminum oxide and 15 parts of water; The preparation method of the ceramic mud comprises the following steps: (a) calcining quartz sand and feldspar at 1000° C. for 1 hour and then crushing them into powder; (b) pulverizing kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate into powder; (c) Mix the calcined raw materials and powder, add water and stir evenly, and then directly shape them without heating or boiling.

[0091] Comparative Example 2 This comparative example is a traditional ceramic mud, which is prepared from the following raw materials in parts by weight: 45 parts of kaolin, 2 parts of quartz sand, 4 parts of feldspar, 5 parts of calcium carbonate, 3 parts of clay, 4 parts of talc, 3 parts of wollastonite, 3 parts of magnesium carbonate, 3 parts of aluminum oxide and 10 parts of water; The preparation method of the ceramic mud comprises the following steps: (a) calcining quartz sand and feldspar at 1200° C. for 2 hours and then crushing them into powder; (b) pulverizing kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate into powder; (c) Mix the calcined raw materials and powder, add water and stir evenly, and then directly shape them without heating or boiling.

[0092] Experimental example Obtain the ceramic mud prepared in Example 1 and Comparative Examples 1-2 respectively; The ceramic clay is used to mold and fire ceramic products, and the thermal conductivity and mechanical strength thereof are measured; Group Thermal conductivity (W / m·K) Mechanical strength (MPa) Example 1 0.8 65 Comparative Example 1 1.2 50 Comparative Example 2 1.1 45 Table 2 Comparison of ceramic product performance Group Thermal stability Chemical resistance Cost-effectiveness Example 1 excellent good high Comparative Example 1 middle middle middle Comparative Example 2 Difference Difference Low Table 3 Comparison of preparation process efficiency Group Preparation time (h) Energy consumption (KWh) Yield rate (%) Example 1 3.5 2.5 95 Comparative Example 1 5.0 4.5 80 Comparative Example 2 4.0 3.8 85 From Tables 1 to 3, we can see that: The ceramic mud prepared by the technical solution of the present application and the comparative example has significant differences in thermal conductivity and mechanical strength. The ceramic mud prepared by the technical solution of the present application has lower thermal conductivity and higher mechanical strength. In addition, the technical solution of the present application also shows better performance in terms of thermal stability, chemical resistance, cost-effectiveness and preparation process efficiency.

[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

[0094] The above descriptions are only some preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present invention.

Claims

1. An energy-saving medium-temperature high-white ceramic mud, characterized by: The invention is prepared from the following raw materials in parts by weight: 42.2-43.0 parts of kaolin, 2.0-3.0 parts of quartz sand, 4.0-6.0 parts of feldspar, 6.4-7.0 parts of calcium carbonate, 4.0-6.0 parts of clay, 4.8-5.2 parts of talc, 4.0-5.0 parts of wollastonite, 4.0-5.0 parts of magnesium carbonate, 4.0-6.0 parts of aluminum oxide and 12.3-13.0 parts of water.

2. The energy-saving medium-temperature high-white ceramic mud according to claim 1, characterized in that: It is made from the following raw materials in parts by weight: 42.2 parts of kaolin, 2.0 parts of quartz sand, 4.0 parts of feldspar, 6.4 parts of calcium carbonate, 4.0 parts of clay, 4.8 parts of talc, 4.0 parts of wollastonite, 4.0 parts of magnesium carbonate, 4.0 parts of aluminum oxide and 12.3 parts of water.

3. The energy-saving medium-temperature high-white ceramic mud according to claim 1, characterized in that: It is made from the following raw materials in parts by weight: 43.0 parts of kaolin, 3.0 parts of quartz sand, 5.0 parts of feldspar, 7.0 parts of calcium carbonate, 6.0 parts of clay, 5.2 parts of talc, 5.0 parts of wollastonite, 5.0 parts of magnesium carbonate, 6.0 parts of aluminum oxide and 13.0 parts of water.

4. The energy-saving medium-temperature high-white ceramic mud according to claim 1, characterized in that: It is made from the following raw materials in parts by weight: 42.8 parts of kaolin, 2.6 parts of quartz sand, 5.2 parts of feldspar, 6.8 parts of calcium carbonate, 5.1 parts of clay, 5.0 parts of talc, 4.5 parts of wollastonite, 4.5 parts of magnesium carbonate, 4.5 parts of aluminum oxide and 13.0 parts of water.

5. The energy-saving medium-temperature high-white ceramic mud according to claim 1, characterized in that: The alumina is a combination of one or more of α-alumina, β-alumina and γ-alumina.

6. The energy-saving medium-temperature high-white ceramic mud according to claim 5, characterized in that: The alumina is a mixture of α-alumina and β-alumina, and the weights of the α-alumina and the β-alumina are equal.

7. The energy-saving medium-temperature high-white ceramic mud according to claim 5, characterized in that: The alumina is γ-alumina, and by weight, the feldspar is 4.0 parts and the alumina is 6.0 parts.

8. The energy-saving medium-temperature high-white ceramic mud according to claim 5, characterized in that: The alumina is α-alumina, and the purity of the α-alumina is greater than 99.5%.

9. A method for preparing energy-saving medium-temperature high-white ceramic mud according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. The quartz sand and feldspar are calcined at high temperature for 30 to 60 minutes and then crushed into powder to obtain a calcined raw material; S2. The kaolin, calcium carbonate, talc, wollastonite and magnesium carbonate are crushed into powder; S3. The calcined raw materials, powder, water, mixed, stirred, heated, boiled over high heat for 1.5 to 2 hours, then simmered for 3 to 6 hours as the aqueous phase; S4. The clay and alumina were mixed and stirred for 10-20 minutes and kept warm at 70°C to 80°C in a water bath as a mud phase; S5. Slowly pour the aqueous phase into the mud phase, add calcium carbonate and mix, stirring at 150 ℃ ~ 200 ℃ for 20 to 30 minutes; S6. Finally cool to room temperature.

10. The method for preparing energy-saving medium-temperature high-white ceramic mud according to claim 9, characterized in that: In step S2, the particle size of the powder is less than 400 mesh, and the powder is ball-milled in a ball mill for 2 to 4 hours to improve the uniformity and plasticity of the raw material; the ball-milled powder is sieved through a 0.5 to 1.0 mm sieve to ensure the consistency of the powder fineness.